Predictors of not working among treatment-seeking UK veterans: a cross-sectional study. Issue 1 (14th May 2020) - Hendrikx, Laura Josephine; Ross, J; Armour, C; Murphy, D
Abstract : Introduction: Many veterans do well reintegrating to civilian life following military service. Yet, many face difficulties in finding and securing work. Veterans are more likely than civilians to experience work difficulties, but there remains little research investigating contributing factors, particularly among samples of treatment-seeking veterans. As such, the study examines predictors of not working among UK treatment-seeking veterans. Design: The study employed a cross-sectional design. Methods: Of 667 treatment-seeking UK veterans, 403 ( Mage =50.94) provided information on a range of demographic variables, military-related experiences, the total number of physical health conditions and mental health outcomes. Work status was categorised as not working due to illness ( Mage =48.15), not working due to other reasons ( Mage =61.92) and currently working ( Mage = 46.13). Results: Prevalence rates of not working was 69%. Not working was predicted by a greater number of physical health problems as well as more years since leaving the military. Not working due to poor health was independently predicted by symptoms of post-traumatic stress disorder (PTSD) and younger age, while not working due to other reasons was predicted by older age. Conclusions: The study revealed that treatment-seeking veterans of younger age with a high number of physical health difficulties, symptoms of PTSD and more years since leaving the military are most at risk of not working due to ill health. The findings have important implications for identifying veterans most at risk of not working and offer the opportunity to tailor rehabilitation programmes to promote successful veteran reintegration into civilian life.